Mapping Corporate Governance: Exploring the Adaptation of Regulatory Frameworks in African Markets - Abubakar Balarabe Karaye (Eurasian Journal of Management & Social Sciences, 2024)
This study aims to provide a comprehensive review of the sources of corporate governance regulations in Africa, by examining their origins and adaptation within the context of diverse African markets. While acknowledging the influence of regulatory frameworks from developed countries, this study focuses on the unique challenges and dynamics shaping corporate governance practices in the African markets. To achieve this aim, an in-depth analysis of key regulatory sources and their implementation across various African nations was done by reviewing the literature and the regulatory frameworks. The study shed light on the interplay between global standards and local realities, focussing on the evolving corporate governance landscape in Africa. By synthesizing existing literature and empirical insights from 2018 to 2023, the study offers valuable perspectives, emphasizing the need for tailored approaches that address continental disparities, challenges, and national culture in the adoption of corporate governance regulations across diverse African jurisdictions.